PREVALENCE OF NEUTRALIZING ANTIBODIES AGAINST POLIOVIRUS 1, 2, AND 3 IN HEALTHCARE PROFESSIONALS AGED 20-50 YEARS - José Cassio de Moraes; Maria Josefa Penon Rujula; Marcelo Otsuka (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To describe the prevalence of neutralizing antibodies against poliovirus (PV1, PV2, and PV3) in blood samples of healthcare professionals aged 20 to 50 years. Methods: Health professionals who serve children at Darcy Vargas Children's Hospital and the Department of Pediatrics of Irmandade da Santa Casa de São Paulo. The sample size was calculated at 323 participants. The Mantel-Haenszel chi-square was used to verify differences between groups. The neutralization reaction detected human poliovirus antibodies. For susceptible individuals, vaccination with the inactivated+triple acellular polio vaccine was performed, and neutralizing antibodies were re-dosed after one week. Results: 333 professionals were studied - 92.8% were immune to poliovirus 1, 86.5% to poliovirus 2, and 63.3% to poliovirus 3; 37% had titers less than 1:8 for any serotype, 5;1% had titers below 1:8 for all three. Vaccination with inactivated polio vaccine was performed for susceptible participants, and neutralizing antibodies were dosed after one week, showing increased titers for all polioviruses. Conclusions: Despite the detection of a significant percentage of individuals with low poliovirus antibody titer, the challenge with vaccination demonstrated immune response compatible with poliovirus immunity.